(untitled) (Journal of Plant Disease Sciences, 2019)
Effect of fungicides, botanicals, and bio-agents tested under field condition to minimize the fruit drop of Nagpur mandarin ambiabahar at two locations over the two years and results revealed that all the treatments were significantly effective for suppression of the fruit drop during both the years. The efficiency of sprays revealed that, the minimum fruit drop was recorded in carbendazim (11.61%) which was significantly reduced the fruit drop over rest of treatments during both the years followed by copper oxychloride (12.32 %) and curzate M-8 (14.32%). Among the botanical’sneem seed extract (5%) was found more effective in reducing the fruit drop incidence (18.25%) as compared to Bougainvillea spectabilis (17.48 %).The fungitoxic effects of all bio-agents and their combinations were found significantly effective for reduction of fruit drop over control. Bacillus subtilis (0.5%) recorded maximumreduction in fruit drop (35.50 %) with incidence of (16.60%).